Public Health Services of Novonikolaevsk in Summer of 1918 — in Autumn of 1919 - S. О. Vishnevsky (Научный диалог)
The article is devoted to the health care of Novonikolaevsk in the conditions of the civil war. Based on reference books, periodicals and previously unpublished archival sources, the author considers the development of healthcare in Novonikolaevsk in the prerevolutionary period. The process of creating new bodies and institutions that functioned in the summer of 1918 — in the autumn of 1919 is traced. The general sanitary-epidemic condition of the city is characterized. It was established that the health care system of Novonikolaevsk, the beginnings of which were laid in the first two decades after the city was founded, was not ready for the challenges of wartime. The facts are cited indicating that medical institutions could not cope with the influx of military personnel and refugees, many of whom were sick and were carriers of typhus. It was found that the sudden overpopulation of the city, the unsanitary conditions prevailing there, the lack of hospital beds, clean linen and medicines prevented not only the elimination, but even the simple localization of the epidemic. It was concluded that the pre-revolutionary health care system of Novonikolaevsk could not quickly adapt to the emergency conditions of the civil war, as a result of which, by November 1919, the local authorities almost completely lost control over the sanitary and epidemic situation in the city.